2013
DOI: 10.1299/jtst.8.294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrophobic-Spot Periphery and Subcooling on Nucleate Pool Boiling from a Mixed-Wettability Surface

Abstract: The effect of subcooling and length of hydrophobic-spot periphery on nucleate pool boiling heat transfer from TiO 2 -coated surface with and without PTFE (polyetatafluoroethylene) hydrophobic circle spots at intermediate heat flux has been examined. The experiments are performed with liquid subcooling ranging from 0-20 K and heat transfer block used were TiO 2 -coated copper block with a PTFE hydrophobic circle spot with various diameters with total area of PTFE being constant. Bubble nucleation and behavior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The bubble behavior (namely, the departure frequency and diameter) was recorded by using a high speed camera (Phantom v.4.3 with a Nikkor 180 mm f/2.8D AF lens) under the subcooled (DT b > 0 C) and, for comparison, saturation conditions (DT b ¼ 0 C). Consistent with our previous experimental results [19], the first sign of periodic bubble generation was detected at "negative" superheat DT w ¼ À2.6 C. In contrast, bubbles did not appear until DT w ¼ 4.6 C under the saturation condition as shown in Fig. 4(b).…”
Section: Experiments Apparatus and Proceduressupporting
confidence: 92%
See 2 more Smart Citations
“…The bubble behavior (namely, the departure frequency and diameter) was recorded by using a high speed camera (Phantom v.4.3 with a Nikkor 180 mm f/2.8D AF lens) under the subcooled (DT b > 0 C) and, for comparison, saturation conditions (DT b ¼ 0 C). Consistent with our previous experimental results [19], the first sign of periodic bubble generation was detected at "negative" superheat DT w ¼ À2.6 C. In contrast, bubbles did not appear until DT w ¼ 4.6 C under the saturation condition as shown in Fig. 4(b).…”
Section: Experiments Apparatus and Proceduressupporting
confidence: 92%
“…The subsequent vertical growth ultimately led to separation from the surface due to the increased buoyancy force. Immediately following the bubble emission, as can be seen in the figure, the PTFE area still remained blanketed with cone-shaped vapor layer irrespective of the surface temperaturedphysically defined as local film boiling [19]das part of the bubble was apparently left on the surface, which constitutes essentially zero waiting period for bubble generation. It is worth noting that, instead of being completely vapor-capped, the PTFE portion of the surface seemed to be covered with small discrete bubbles under the saturation condition, as shown in Fig.…”
Section: High-speed Visualization Of Bubble Behaviormentioning
confidence: 91%
See 1 more Smart Citation
“…Their superbiphilic surfaces also showed significant HTC enhancement for low superheat values, up to 10 times the HTC of a simple biphilic surface at 5K of superheat 58 . Other biphilic and superbiphilic surfaces have been synthesized and have demonstrated site-selective nucleation 203,251 and enhanced boiling heat transfer 44,235,[251][252][253] for water. For design considerations of these surfaces, it has also been shown that the size and pitch of the hydrophobic dots are the dominant parameters at low heat fluxes and that, at a high heat flux, a high number of hydrophobic dots could result in decreasing the value of the CHF 44,235,[251][252][253] .…”
Section: Spatial Patterning Of Wettability To Improve Both Htc and Chfmentioning
confidence: 99%
“…This improved the number of active nucleation site densities and caused, at low heat flux levels, an approximately 200% enhancement on the heat transfer coefficient. Tashiro et al (2012) and Suroto et al (2013) used hydrophilic TiO 2 coating (0 • ) and hydrophobic Teflon (127 • ) to investigate the wettability effect on pool boiling heat transfer of water. Photographs of the tested surfaces and their corresponding CAs are illustrated in Fig.…”
Section: Fig 12mentioning
confidence: 99%